Phyto-sesquiterpene lactones DET and DETD-35 induce ferroptosis in vemurafenib sensitive and resistant melanoma via GPX4 inhibition and metabolic reprogramming. (April 2022) - Chang, Meng-Ting; Tsai, Li-Chu; Nakagawa-Goto, Kyoko; Lee, Kuo-Hsiung; Shyur, Lie-Fen
Abstract: Acquired resistance to vemurafenib (PLX4032) is a thorny issue in BRAF V600E mutant melanoma therapy. Ferroptotic programmed cell death is a potential strategy for combating therapy-resistant cancers. This study uncovers the adaptation and abnormal upregulation of PUFAs and bioactive oxylipin metabolism in PLX4032 resistant melanoma cells. Phyto-sesquiterpene lactone, DET, and its derivative, DETD-35, induced lipid ROS accumulation and triggered ferroptotic cell death in PLX4032 sensitive (A375) and resistant (A375-R) BRAF V600E melanoma cells by reprogramming glutathione and primary metabolisms, lipid/oxylipin metabolism, and causing mitochondrial damage in which DETD-35 showed superior efficiency to DET. We discovered that DET and DETD-35 are a new type of GPX4 enzyme inhibitor through non-covalent binding. This study provides new insight into the therapeutic mechanisms of both DET and DETD-35 to combat PLX4032 sensitive/resistant BRAF V600E mutant melanomas via targeting GPX4 and ferroptosis. Graphical Abstract: ga1 Highlights: PLX4032 resistant melanoma shows upregulated PUFAs and derived bioactive oxylipins. DET and DETD-35 impair mitochondria and reprogram metabolic pathways in melanoma. DET and DETD-35 trigger ferroptosis via directly inhibiting GPX4 activity. Combining DET/DETD-35 and PLX4032 is promising for drug-resistant melanoma.